The application of asymptotic analysis for modes I and III semi-infinite wedge solutions to a circumferentially notched shaft - Duó, P; Korsunsky, A; Hills, D (Professional Engineering Publishing, 2005)
Mode I and mode III solutions for sharp notch roots are derived and compared with representative full-field solutions. The example geometry studied is a circumferentially notched shaft, loaded in both tension and torsion. The calibration for the notch root intensity factors has been carried out using the finite element method. The combined effects of tension and torsion have been briefly considered as an example.